Spindle cell lipoma of the jejunal mesentery - Ryuji Okubo; Takuro Kazama; Masaki Nio (Elsevier, 2020)
3-year-old girl with diarrhea was found to have an abdominal mass when she visited a hospital. The mass had a smooth margin and clear boundary, with an irregular internal echogenicity, showing patches and streaks. The mass showed low signal intensity on T1-weighted images and high signal intensity on T2-weighted images, and the images were disturbed by the fat component inside the mass. The origin of the tumor was the mesentery. The tumor had a wide base and was contiguous with the small intestine. The tumor, including one side of the mesentery, was resected while the intestinal tract was kept intact. Fibroblast-like spindle cells were arranged in characteristic parallel arrays, with highly variable amounts of mature adipocytes in a background of collagen bundles, myxoid stroma. On immunohistochemical analysis, the spindle cells were strongly positive for CD34 but were negative for S100. Spindle cell lipoma (SCL) is a benign soft tumor, and distinguishing SCLs from liposarcomas is sometimes difficult. SCLs commonly occur in the posterior cervical region and shoulders of old and middle-aged men. Only three cases of SCLs in children have been reported.